Journal of Geography & Natural Disasters - OMICS International (OMICS International, 2026)
Journal of Geography and Natural Disasters publishes articles related to Damage Assessment, Disaster Response, Disasters Journal, Environmental Degradation, Geographic Information System, Natural Geography, Natural Hazards, Physical Geography, Volcanic Eruption Geography and Natural Disasters. Geography (Greek word geographia, earth description) is the study of earth and its land and water features, inhabitants and phenomena. Geography has been called "the world discipline". Geography is divided into two main branches-Human geography and Physical geography. A Natural Disaster may be defined as the effect of Natural hazards which leads to human, environmental or financial losses.
Keywords: Geografía; Desastres naturales; Revistas depredadoras; Predatory journals